Can combined blood neutrophil to lymphocyte ratio and C-reactive protein be used for diagnosis of spontaneous bacterial peritonitis?. Issue 2 (3rd April 2018) - Mousa, N; Besheer, T; Abdel-Razik, A; Hamed, M; Deiab, AG; Sheta, T; Eldars, W
Abstract: Background and objective: Spontaneous bacterial peritonitis (SBP) is diagnosed by the presence of ≥250 polymorphonuclear neutrophils (PMN)/mm 3 in the ascites and the absence of surgically treatable cause of intra-abdominal infection. Blood neutrophil lymphocytic ratio (NLR) is an inexpensive and simple test for inflammation. C-reactive protein (CRP) is an inflammatory marker used for the diagnosis and follow-up of many diseases and morbidities. We aimed to evaluate the clinical utility of combined blood NLR and CRP as a non-invasive test for SBP diagnosis. Methods: Blood NLR was calculated, and CRP value determined in 180 cirrhotic patients with ascites (126 with and 54 without SBP). Sensitivity and specificity of combined blood NLR and CRP values for SBP diagnosis were estimated by receiver operator characteristic curve. Results: Both blood NLR and CRP values were significantly higher in SBP ( p < 0.001). For SBP diagnosis, a blood NLR of >2.89 had a sensitivity 80.3% and specificity 88.9%. CRP >11.3 mg/dL had a sensitivity 88.9% and specificity 92.6%. In logistic regression analysis, combined blood NLR and CRP had a sensitivity 95.1% and specificity 96.3% at the same cut off values. Conclusions: Combined NLR and CRP could be used as a novel, simple, low-cost, non-invasive test for SBP diagnosis.